THE INFLUENCE OF E-CONSUMERS' MOTIVATION TOWARD ATTITUDE AND SATISFACTION: The Uses and Gratifications Approach - Hermawan, Herry (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
This study examines the influences of entertainment, informativeness, and Web irritation on attitude toward online shopping and satisfaction in online shopping. Particularly, satisfaction in online shopping is explored as the consequences of attitude toward online shopping, while informativeness, entertainment, and irritation are the antecedents of attitude toward online shopping. Data were collected through a quantitative study applying an online questionnaire carried out in 2020, using a representative sample. Findings showed that attitude toward online shopping is determined by entertainment, while informativeness does not significantly affect consumers’ attitude toward online shopping. Web irritation was also found to be of equal importance in influencing the formation of consumers’ attitudes toward online shopping but in a negative manner. This suggests that Web irritation on online shopping sites has a significant influence on consumers. If online shopping sites are irritating, then consumers form negative attitudes toward online shopping. This study also found that consumers’ satisfaction to shop online is determined by their attitude toward online shopping. The findings contribute to the evolution of the Uses and Gratification Theory, particularly in online shopping in developing countries like Indonesia. This study provides implications to e-business, marketers, and website system developers of online shopping sites dealing with products. To cite this article (7th APA style):Hermawan, H. (2021). The influence of e-consumers’ motivation toward attitude and satisfaction: the Uses and Gratifications approach. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 52-63. http://dx.doi.org/10.36782/jcs.v1i1.2133